L’histoire photographique de l’Amérique selon Robert Taft (Photography and the American Scene, 1938) - François BRUNET (E-REA)
This article examines the meanings and uses of “social history” and “historical value” in Robert Taft’s Photography and the American Scene, A Social History 1839-1889 (1938), a classic text still received as a major reference on 19th-century American photography and yet rarely questioned in its own right as a historical enterprise. We briefly address the context of the book, before analyzing its main discursive categories, starting with Taft’s painstaking collection of “firsts” in American photography (first portrait, first use of photography on Western exploration, and so on). Two implicit concepts at work in the book are isolated: the photograph as “event”, i.e. as history-making, the two main examples being Mathew Brady’s portraits of Abraham Lincoln, supposed to have influenced the 1860 election, and William H. Jackson’s 1871 photographs of Yellowstone, supposed to have “won” the passing of the National Park bill; and then the photograph as “document”, i.e. as visual evidence of the American “scene”, which Taft encourages his reader to collect and study as if to promote the popular practice of history. The epic and democratic dimensions of Taft’s social history are shown to merge in Taft’s treatment of Mathew Brady, “historian with a camera”, as a focal point and a kind of paradigm for photographic history.